Tinjauan Hukum Pidana Pada Kasus Laka Lantas Atas Dampak Kerusakan Jalan - Selvin Triansih; Surya Perdana; Alpi Sahari (Journal Recht (JR), 2022)
Accidents often occur on the highway, apparently not only due to driver factors and natural factors, but also because of the number of damaged roads such as potholes, cracks, uneven surface of the road, which can cause casualties for motorists. Many cases of death of motorists because they avoid potholes, causing loss of life and property of the government as the organizer of the road should be held liable for criminal liability for negligence to repair the road. This study aims to analyze the legal protection of motorized motorists who experience accidents due to the impact of road damage and the accountability of road organizers in the case of traffic accidents due to the impact of road damage. The results of this study indicate that the legal protection for motorized motorists who have accidents due to the impact of road damage is based on the formulation of Law Number 22 Year 1999 concerning Road Traffic and Transportation Article 240 letter b, which becomes the accident victims of road traffic can file a lawsuit against the party that caused the loss, that the criminal liability of the road operator against victims due to road damage, in Law Number 22 Year 2009 concerning Traffic and Road Transportation in principle, the organizer of traffic and road transportation is the responsibility of the state.